2020
DOI: 10.1038/s41419-020-03167-5
|View full text |Cite
|
Sign up to set email alerts
|

Parp3 promotes astrocytic differentiation through a tight regulation of Nox4-induced ROS and mTorc2 activation

Abstract: Parp3 is a member of the Poly(ADP-ribose) polymerase (Parp) family that has been characterized for its functions in strand break repair, chromosomal rearrangements, mitotic segregation and tumor aggressiveness. Yet its physiological implications remain unknown. Here we report a central function of Parp3 in the regulation of redox homeostasis in continuous neurogenesis in mice. We show that the absence of Parp3 provokes Nox4-induced oxidative stress and defective mTorc2 activation leading to inefficient differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 72 publications
(85 reference statements)
1
11
0
Order By: Relevance
“…PARP1 and PARP3 were implicated in regulating mitochondrial morphology [20,85,86]; hence, we assessed the possible involvement of PARP1 and PARP3. Silencing PARP1 in scPARP2 and shPARP2 C2C12 cells (Figure 11A) led to the loss of PARP1 auto-PARylation (Figure 11A).…”
Section: Parp1 and Parp3 Are Not Involved In Mitochondrial Fragmentation Elicited By The Silencing Of Parp2mentioning
confidence: 99%
“…PARP1 and PARP3 were implicated in regulating mitochondrial morphology [20,85,86]; hence, we assessed the possible involvement of PARP1 and PARP3. Silencing PARP1 in scPARP2 and shPARP2 C2C12 cells (Figure 11A) led to the loss of PARP1 auto-PARylation (Figure 11A).…”
Section: Parp1 and Parp3 Are Not Involved In Mitochondrial Fragmentation Elicited By The Silencing Of Parp2mentioning
confidence: 99%
“…Poly (ADP-ribose) polymerase 3 (Parp3) is a member of ARTD (Parp) family which can synthesize poly (ADP-ribose) at the expense of NAD + [30]. Previous studies showed that Parp3 was involved in the cellular response to DNA damage [31], mitotic progression [32], chromosomal rearrangements [33], the regulation of redox homeostasis [34] and tumor aggressiveness [35]. Moreover, Parp3 inhibitor ME0328 was found to cause cell cycle arrest in breast cancer cells [36].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, identifying the PARP12-interacting mitochondrial proteins would help us to understand the underlying mechanisms. Some pathways that are independent of PARylation may also participate in maintaining mitochondria homomasis, in light of not all PARPs family members exert its role by PARylation [ 38 , 39 ]. Besides, given that some RNA binding proteins (RBPs) have been identified as essential for adipogenesis and thermoregulation [ 40–42 ], as an RBP, PARP12 may also exert its function by affecting RNA processes and post transcription.…”
Section: Discussionmentioning
confidence: 99%